Teachers' motivation to choose teaching and remain in the profession: A comparative mixed methods study in Jamaica, Poland and Turkey - Onyefulu, Cynthia; Madalinska-Michalak, Joanna; Bavli, Bunyamin (SAGE PUBLICATIONS LTD, 2023)
The comparative, mixed methods international and cross-cultural study aimed to determine the factors that motivated teachers in Jamaica, Poland and Turkey to choose teaching as a career and ascertain what motivated the teachers at different stages to remain in teaching. Data were collected through the use of the questionnaire, which experts validated and had an overall reliability co-efficient of 0.77 and focus group interviews. A total of 186 teachers participated in the quantitative phase of the study, whilst 75 participated in the qualitative phase. The findings showed that extrinsic, intrinsic, and altruistic motivation, roles and responsibilities, and opportunities were the main reasons teachers in the three countries chose the teaching profession. Teachers in the different stages of their careers remain in the profession because of a strong sense of vocation, a passion for teaching, a need to make a positive difference in students' life, job satisfaction, and connected with its rewards of being a teacher. It was recommended that researchers interested in this area could use a more representative sample size to generalize the findings.
Keywords: Choosing teaching; teacher motivation; teacher retention; teaching profession; PRESERVICE TEACHERS; EDUCATION; CAREER; STUDENTS; SATISFACTION; PERCEPTIONS; COMMITMENT; REASONS; LEARN; STAY; Education & Educational Research